The Return to Capital in the British Motor Vehicle Industry, 1896–1939 - Lewchuk, Wayne (Business History, 1985)
The objective of this paper is to examine the financial history of the British motor vehicle industry betweem 1896 and 1939. The study is based on data collected from 38 firms which issued shares publicly or were required to publish balance sheets. These firms represent the majority of British firms engaged in the quantity production of motor vehicles. ...Our interest in the industry's financial history, and in particular, the return to capital of firms using British production techniques was stimulated by the long standing argument that since 1870 British levels of productivity have lagged behind others countries, particularly the United States. –Introduction